3D imaging added value in the treatment and diagnosis of displaced intra-articular calcaneal fractures (DIACF): measuring the orientation of the posterior talo-calcaneal facet in the space. Issue 2 (3rd February 2022) - Misselyn, Dominique; De Buck, Stijn; Nijs, Stefaan; Matricali, Giovanni; Schepers, Tim
Abstract: Purpose: Measure the reduction quality of calcaneal fractures on 3 D segmented images. Methods: The Ethics Review Board approved this study and written informed consent was collected from all patients. Bilateral CT scans of fifty-four patients with unilateral displaced calcaneal fracture were obtained before and after osteosynthesis. Orientation angle of the posterior subtalar joint facet (PTC) of displaced intra-articular calcaneal fractures of 54 patients was measured on segmented 3 D images before and after surgery and compared to the uninjured side. This orientation angle (OAC) is the average of every normal vector of each point of the PTC, as compared to the main calcaneal axis (calculated by first principal component analysis). The PTC is a well-known anatomical structure, relatively easy to identify on 3 D imaging. Results: This OAC angle was low before surgery (mean= 95°, std dev= 6°), statistically significantly different from the uninjured side value, p < 0.001. The OAC angle of the operated bone was nearly equal to the uninjured side (mean= 103°, std dev= 5°), without any statistically significant difference between postoperative values and uninjured side values. We found linear correlation between the quality of the reduction when assessed with this OAC and the functional score (AOFAS) (Adjusted R 2 =0.62, p = 0.04). Conclusions: This angle seems to be useful to quantify the quality of the operative reduction of displaced intra-articular calcaneal fractures.